DAMPAK STRUKTUR MODAL TERHADAP KINERJA KEUANGAN DI SEKTOR PERDAGANGAN INDONESIA - Ranila Suciati; Siti Hidayati; Kery Utami (Program Studi Ekonomi Islam, Fakultas Ekonomi dan Bisnis - Universitas Syiah Kuala, 2021)
A composition or a liability structure is the understanding of a company's capital structure. The purpose of this study is to analyze the capital structure and financial performance from 2015 to 2018 (4 years) in the Indonesian Trade Sector. The sample of this study was processed from annual report data of Indonesian Trade Sector companies listed on the Indonesia Stock Exchange, this is in accordance with the objectives of this study. The analytical method in this study uses panel data regression. The relationship between capital structure and financial performance will be revealed from this study. The independent variable is the capital structure will be proxied with a debt to equity ratio (DER), debt to asset ratio (DAR), and longterm debt ratio (LTDR). And for the dependent variable that is financial performance will be proxied by Return on Equity (ROE). Research on trade sector companies in Indonesia produces a R square model value of 0.9291 which means that 92.91% of financial performance is explained by the variables of this study.